Knowledge of midwives regarding traditional practices used during intrapartum period in a selected hospital in Gauteng - Ngunyulu, Roinah Nkhensani (University of Pretoria, 2023)
Dissertation (MSc (Nursing Science))--University of Pretoria, 2022.